Fatores relacionados à ocorrência do Near Miss Materno - Brito, Jaqueline Guimarães Elói de (2023)
Introduction: Maternal Near Miss (MNM) is defined as a woman who nearly died but survived a complication that occurred during pregnancy, childbirth or within 42 days of termination of pregnancy. Objective: Evaluate the factors related to the occurrence of a Maternal Near Miss. Material and methods: Utilize a quantitative and transversal research with an analytical approach. The sample consisted of 89 postpartum women hospitalized in a high-risk maternity hospital located in Sergipe, Brazil. The maternal sociodemographic variables, prenatal care, childbirth and the immediate postpartum period were analyzed. For statistical analysis, the quantitative variables were analyzed using mean, standard deviation, minimum and maximum values. Qualitative/categorical variables were analyzed using univariate and bivariate techniques in the IBM® SPSS - Statistical Package for the Social Sciences. Associations between qualitative/categorical variables were estimated using Pearson's Chi-square and Fisher's exact tests, calculating the Prevalence Ratio (PR) with their respective 95% Confidence Intervals. Results: Most women were of ages between 18 and 34 years (74.15%; n= 66) during pregnancy; (95.50%; n= 85) declared themselves to be non-white, residents of a urban area (60.67%; n= 54), attended elementary school (64.04%; n= 57) and had a family income of > 1 minimum wage (MW) and ≤ 2 SM (57.30%; n= 51). 97.75% (n=87) of the evaluated puerperal women were classified as MNM by the criteria proposed by Waterstone et al., (2001). In these hypertensive syndromes (severe PE, Eclampsia and HELLP Syndrome) were the most frequent cases. Only two patients met the WHO criteria: puerperal hysterectomy due to infection or hemorrhage (2.24%; n= 2). Conclusion: Hypertensive disorders stand out among the causes of MNM, which highlights the need for improvements in the screening and treatment of high blood pressure in pregnant women in prenatal services, as well as adequate obstetric care for the most severe cases.